G495(P) Trends in long-stay patients in paediatric intensive care unit. (27th April 2016) - Kanthimathinathan, H; Plunkett, A; Scholefield, B; Pearson, G; Morris, K
Abstract : Background and aims: Long-stay patients in paediatric intensive care units (PICU) are associated with disproportionately high healthcare resource utilisation and unfavourable outcomes. Increase in long-stay admissions and bed-occupancy have been reported elsewhere but not in the UK. Methods: We performed a retrospective analysis of PICU admissions over the last 19 years. Long-stay admissions [length of stay ≥ 28 days] were analysed over 4 different study-periods [1996–2000, 2001–2005, 2006–2010 and 2011–2014]. Chi-square test for trends used for significance tests for trends in proportions. Results: 22, 059 admission episodes accounted for 108, 522 bed-days. 521 long-stay episodes accounted for 30, 052 bed-days. Proportion of long-stay admissions and bed-days increased from 1.2% and 19% respectively in 1996–2000, to 3.6% and 36% in 2011–2014 [p < 0.001, Table 1 ]. Long-stay admissions were associated with significantly higher mortality rate (20–31%) throughout the study period [p < 0.001, Table 1 ]. Conclusions: We found an increasing trend in proportion of long stay patients and bed occupancy. If nationwide figures confirm this trend, PICU capacity planning for the future should take this into account.